Kesalahan Siswa Dalam Menyelesaikan Soal-Soal Trigonometri Kelas Xi Smk Muhammadiyah Kartasura Tahun 2016/2017 - Safitri, Marlina Wulan; , Rita Pramujiyanti Khotimah,S.Si, M.Sc (2017)
The purpose of this study is to describe the errors exprerienced by students and and the cause of students' errors in resolving problem of the trigonometric of sum and differene two anggle and similarity trigonometric.The type of this research is descriptive qulittive, with the subjects were students of class XI MB SMK Muhammadiyah Kartasura year 2016/2017. Technique of data to using the tes method, interviews, and dokumentation. Data validation was done by triangulation technique by comparing the test data, interviews, and dokumentation. Data analysis technique by mean of data reduction, data presentation, and verification of data and making concusions. Base on the analysis we concluded that (1) 20 % of student experienced a reading in question (2) 42 % of student experienced a comprehention in question. (3) 51 % of student experienced a transformation in question. (4) 51 % of student experienced a proces skill in question (5) 87 % of student experienced a encoding in question Factors which cause the ability of low derstanding, not accustomed to writing down what is known and asked, students forget the formula, students can not pour the results in words and less conscientious in completing the sheer number and the difference of two angles and trigonometric equations. Keywords: Errors, carefulnes, trigonometric